Efecto de interacción del nitrógeno y potasio y su influencia sobre parámetros de crecimiento en el cultivo de banano - Renteria Rodriguez, Yuber Stalin (Machala : Universidad Técnica de Machala, 2019)
The Banana is the most important crop in the economy of Ecuador being agricultural items at national level, the capital income generated contributes to the circulation of foreign exchange in the country. The absence of information created in relation to the nutritional demands of the crop in our field of professional action limits us to using information from other banana producing countries, however, we cannot assume that the results will be similar when the soil-climatic conditions are completely different. The main objective was to analyze the responses of the crop to the interaction of nitrogen and potassium fertilization in different doses on variables of vegetative growth of the Williams cultivar, banana. The experience was carried out in the experimental farm Santa Inés, which is located within the premises of a technical University of Machala, the same that belongs to the parish El Cambio, canton Machala, province of El Oro. The experimental design was a 4 x 4 factorial arrangement in a completely random block design (DBCA) with four repetitions. Each factor has 4 levels, being the factor 1 Nitrogen (N) and its levels N1 (0 kg of N), N2 (200 kg of N), N3 (400 kg of N) and N4 (600 kg of N). The factor 2 Potassium (K) and its levels K1 (0 kg of K), N2 (350 kg of K), K3 (700 kg of K) and K4 (1050 kg of k), the interaction of these two factors and their levels resulted in 16 treatments: T1 (N1K1), T2 (N1K2), T3 (N1K3), T4 (N1K4), T5 (N2K1), T6 (N2K2), T7 (N2K3), T8 (N2K4), T9 (N3K1), T10 (N3K2), T11 (N3K3), T12 (N3K4), T13 (N4K1), T14 (N4K2), T15 (N4K4), T15 (N3K4), T13 (N4K1), T14 (N4K2), T15 (N3K4), T15 (N3K4). The experimental area is 0.86 Ha, the plants were distributed in a spacing of 1.7m between plants and 2.2m between rows. On the sowing day (dds), 6 plants were randomly selected from the 16 plants of each experimental unit, which were followed until the end of the vegetative stage (173) or inflorescence emission. The experimental plot was carried out considering the cultural practices of the technical management of the crop from its sowing to its productive stage, among these practices are: the design of the irrigation system, control of weeds, pests and diseases. The variables evaluated in this experiment were: 1) Plant Height (PA), 2) Perimeter of Pseudotallo (PP), 3) Foliar Emission (FE) and Foliar Area (FA). At the end of the experiment, the collected data were subjected to a variance analysis using an F test to analyze the effects of the evaluated treatments. At the end of the evaluation period (end of the reproductive stage) treatments with significant effects were found, then the relationship between the doses of N and K applied in the case study was analyzed through polynomial regression equations. The evaluation of the relationship between the different doses of N and K and the growth variables (AP), (PP), (EF) and (AF) was carried out by means of a correlation analysis. The data were tabulated and analyzed using AGROESTAT software. As a conclusion we can say that in the first months of life of the banana the element N is fundamental since there were significant differences between its 4 levels statistically speaking, however in the case of K we did not find the same behavior, on the contrary the cases of potassium did not present any difference what indicates that to apply K in the stage of growth is irrelevant when dealing with variables of growth but not of the physiology of the plant.
El Banano es el cultivo más importante en la economía de Ecuador tratándose de rubros agrícolas a nivel nacional, el ingreso de capital que genera contribuye a la circulación de divisas en el país. La ausencia de información creada en relacionada a las demandas nutricionales del cultivo en nuestro campo de acción profesional nos limita a usar información de otros países productores de banano, sin embargo, no podemos asumir que los resultados serán similares cuando las condiciones edafo-climáticas son completamente diferentes. El principal objetivo fue analizar las respuestas del cultivo a la interacción de fertilización nitrogenada y potásica en distintas dosis sobre variables de crecimiento vegetativo del cultivar Williams, banano. La experiencia se llevó a cabo en la granja experimental Santa Inés, que se encuentra ubicada dentro de los predios de una Universidad técnica de Machala, la misma que pertenece a la parroquia El Cambio, cantón Machala, provincia de El Oro. El diseño experimental fue un arreglo factorial 4 x 4 en un diseño de bloques completamente al azar (DBCA)con cuatro repeticiones. Cada factor tiene 4 niveles, siendo el factor 1 Nitrógeno (N) y sus niveles N1 (0 kg de N), N2 (200 kg de N), N3 (400 kg de N) y N4 (600 kg de N). El factor 2 Potasio (K) y sus niveles K1 (0 kg de K), N2 (350 kg de K), K3 (700 kg de K) y K4 (1050 kg de k), la interacción de estos dos factores y sus niveles dieron como resultado 16 tratamientos: T1 (N1K1), T2 (N1K2), T3 (N1K3), T4 (N1K4), T5 (N2K1), T6 (N2K2), T7 (N2K3), T8 (N2K4), T9 (N3K1), T10 (N3K2), T11 (N3K3), T12 (N3K4), T13 (N4K1), T14 (N4K2), T15 (N4K3), T16 (N4K4). El área experimental es de 0.86 Ha, las plantas fueron distribuidas en un espaciamiento de 1,7m entre plantas y 2,2m entre hileras. El día de siembra (dds) fueron seleccionadas al azar 6 plantas de las 16 plantas de cada unidad experimental, las mismas que se les dio seguimiento hasta el término de etapa vegetativa (173) o emisión de la inflorecencia. La parcela experimental fue llevada considerando lleva las prácticas culturales propias del manejo técnico del cultivo desde su siembra hasta su etapa productiva, entre éstas prácticas están: el diseñó del sistema de riego, control de malezas, plagas y enfermedades. Las variables evaluadas en este experimento fueron; 1) Altura de Planta (AP), 2) Perímetro de Pseudotallo (PP), 3) Emisión Foliar (EF) y Área foliar (AF). Al finalizar el experimento los datos recopilados se sometieron a un análisis de varianza empleando un test F para analizar los efectos de los tratamientos evaluados. Al finalizar el periodo de evaluación (Final de la etapa reproductiva) se encuentran tratamientos con efectos significativo, luego se analizó la relación entre las dosis de N y K aplicadas en el estudio de caso a través de ecuaciones de regresión polinomial. Se realizo un test comparación de medias de Tukey al 99% agrupando todos los tratamientos para finalizar, la evaluación de la relación de entre las diferentes dosis de N y K y las variables de crecimiento (AP), (PP), (EF) y (AF) se las realizo mediante un análisis de correlación. Los datos fueron tabulados y analizados utilizando el software AGROESTAT. Como conclusión podemos decir que en los primeros meses de vida del banano el elemento N es fundamental ya que hubieron diferencias significativas entre sus 4 niveles estadísticamente hablando, sin embargo en el caso del K no encontramos el mismo comportamiento, por lo contrario los casos de potasio no presentaron diferencia alguna lo que indica que aplicar K en la etapa de crecimiento es irrelevante tratándose de variables de crecimiento mas no de la fisiología de la planta.
Keywords: BANANO; INTERACCIÓN; NITRÓGENO; POTASIO